2014
DOI: 10.1055/s-0034-1373846
|View full text |Cite
|
Sign up to set email alerts
|

Length of Latency with Preterm Premature Rupture of Membranes before 32 Weeks' Gestation

Abstract: Objective To describe latency for patients with preterm premature membrane rupture (PPROM) between 24 0/7 and 31 6/7 weeks’ gestation. Study Design Secondary analysis of data collected prospectively in a multicenter clinical trial of magnesium sulfate for cerebral palsy prevention. Women with PPROM and fewer than 6 contractions per hour at enrollment who were candidates for expectant management (n=1377) were included in this analysis. Length of latency was calculated in days by subtracting the time of delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…In patients with PPROM before 28 weeks of gestation median latency time was 9 days and 11 days if delivery took place between 28 + 0 to 33 + 6, similar results were presented by A. Peaceman. In a group of 1377 patient's median latency time between 24-28 weeks was approximately 9 days, and between 30-31 weeks was 6 days [18].…”
Section: Discussionmentioning
confidence: 94%
“…In patients with PPROM before 28 weeks of gestation median latency time was 9 days and 11 days if delivery took place between 28 + 0 to 33 + 6, similar results were presented by A. Peaceman. In a group of 1377 patient's median latency time between 24-28 weeks was approximately 9 days, and between 30-31 weeks was 6 days [18].…”
Section: Discussionmentioning
confidence: 94%
“…It is hypothesised that colonisation of the vagina with pathogenic bacteria activate the local and upper (cervical and fetal membrane) innate immune system [ 3 , 6 ], driving an inflammatory cascade [ 7 10 ] that leads to remodelling and disruption of membrane architecture and premature rupture [ 11 ]. In 80% of cases, delivery occurs within 9 days of rupture [ 12 ], during which time the uterine cavity, placenta and fetus are exposed to ascending infection and increased risk of chorioamnionitis and funisitis, which are associated with poor maternal and neonatal outcomes [ 13 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there was no consensus on length of latency to optimize the neonatal morbidity. Peaceman et al( 7 ) assessed the optimal length of latency in patients with PPROM before 32 weeks of gestation in a multicenter randomized study. The authors found that with expectant management, the optimal latency period was approximately 9 days before 28 weeks of gestation, but was significantly shorter in patients with 29-30 weeks of gestation ( 7 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Peaceman et al( 7 ) assessed the optimal length of latency in patients with PPROM before 32 weeks of gestation in a multicenter randomized study. The authors found that with expectant management, the optimal latency period was approximately 9 days before 28 weeks of gestation, but was significantly shorter in patients with 29-30 weeks of gestation ( 7 ) . In another study for all gestational age groups between 24-34 weeks, the best outcomes were in patients with PPROM of 1 to 7 days, and survival was lowest in infants where PPROM was >28 days ( 8 ) .…”
Section: Discussionmentioning
confidence: 99%